2011
DOI: 10.1021/bi200642e
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanisms of Tumor Suppressor P16INK4Aand Their Relevance to Cancer

Abstract: P16INK4A (also known as P16 and MTS1), a protein consisting exclusively of four ankyrin repeats, is recognized as a tumor suppressor mainly due to the prevalence of genetic inactivation of the p16INK4A (or CDKN2A) gene in virtually all types of human cancers. However, it has also been shown that elevated expression (up-regulation) of P16 is involved in cellular senescence, aging, and cancer progression, indicating that the regulation of P16 is critical for its function. Here, we discuss the regulatory mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
235
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(266 citation statements)
references
References 152 publications
(545 reference statements)
10
235
2
4
Order By: Relevance
“…p16 is a tumor suppressor gene that is able to block the G 1 to S phase transition of the cell cycle, thereby inhibiting cell proliferation; in certain tumors, abnormal expression of this gene and protein may also promote the apoptosis of tumor cells. Aberrant p16 underexpression may cause cell proliferation and lead to cancer, the mechanism of which has been confirmed through research conducted in numerous tumor types; p16 inactivation most commonly occurs as a result of gene mutation or 5'CpG island methylation (5). The p16 gene and its protein have been found to be altered in the majority of human primary tumors, including melanoma, head and neck cancers, glioma and gastric cancer (6,7).…”
Section: Introductionmentioning
confidence: 91%
“…p16 is a tumor suppressor gene that is able to block the G 1 to S phase transition of the cell cycle, thereby inhibiting cell proliferation; in certain tumors, abnormal expression of this gene and protein may also promote the apoptosis of tumor cells. Aberrant p16 underexpression may cause cell proliferation and lead to cancer, the mechanism of which has been confirmed through research conducted in numerous tumor types; p16 inactivation most commonly occurs as a result of gene mutation or 5'CpG island methylation (5). The p16 gene and its protein have been found to be altered in the majority of human primary tumors, including melanoma, head and neck cancers, glioma and gastric cancer (6,7).…”
Section: Introductionmentioning
confidence: 91%
“…CDKN2A is inactivated in 95 % of PDAs: in 40 % by intragenic mutations coupled with loss of the second allele (loss of heterozygosity, LOH), in 40 % by homozygous deletion, and in 15 % by epigenetic silencing [30,38,39]. The protein p16 plays a crucial role in cell cycle control as it slows the transition from G 1 phase to S phase.…”
Section: Pancreatic Ductal Adenocarcinomamentioning
confidence: 99%
“…Inactivation of p16 INK4A most frequently occurs through homozygous deletions or aberrant promoter methylation and is an early event in carcinogenesis. It has been suggested that p16 INK4A detection assays might be used to ascertain cancer risk in selected patients and serve as biomarker of earliest stages of cancer development [8,9]. In NSCLC patients with stage I and II higher expression of p16…”
Section: Most Frequently Inactivated Tumor Suppressor Genesmentioning
confidence: 99%